The cult of St. Edward the Confessor, 1066-1399 - O'Brien, E; O'Brien, Emily (2001)
﻿The purpose of this thesis is to determine the popularity of the cult of Edward the Confessor during the period 1066-1399. The first chapter examines the history behind Edward's canonisation. Two elements make it noteworthy: it was the first papal canonisation of an Englishman, and it required two petitions. Because of the monarchy's prominent role in Edward's canonisation, Chapter Two concentrates on royal patronage of the cult. The major obstacle in attaining a clear understanding of the nature of royal devotion to the cult is the monarchy's use of Westminster Abbey, site of Edward's tomb, for royal ceremonies. Chapter Three charts Westminster Abbey's role in the promotion of the saint and his impact in other English ecclesiastical establishments. After discerning the influence of the cult, the focus shifts to secular and hagiographical documents which presented the king. The importance of the documents is that they record any changes in the perception of Edward. Chapter Four looks at the four main vitae written about Edward and detects a metamorphosis in the presentation, deviating from traditional hagiographical forms to a more fantastic, almost fictional account of the king. Chapter Five examines two other types of sources: works produced or commissioned by those who promoted Edward's sanctity and the chronicles which include Edward's reign in their texts. Both types of sources confirm Chapter Four's conclusion that as time passed, Edward became a mythological figure. Chapter Six compares the presentation of Edward with those of political and royal saints in the mid-thirteenth and fourteenth centuries, and finds that the king is an unusual picture of both royal and English sanctity. This study of Edward's cult concludes that though it was used for various political ends and some stories of the saint became popular legends, the cult never attained a popular status.